Strategi untuk Meningkatkan Capaian Target Produksi Departemen Finishing dengan Metode 8 Waste di PT. XYZ - Ferdiansyah, Vicky; Izzhati, Dwi Nurul (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT XYZ faces the problem of not achieving production targets in five departments, especially in the Finishing Department with an achievement of only 54%. This study aims to identify the most dominant waste and provide suggestions for improvement. The methods used include interviews and giving 8 waste questionnaires to five respondents. Then, the most dominant type of waste was determined using a Pareto diagram. After that, root cause analysis was conducted using the 5 Whys method and suggestions for improvement were given. The results show that the dominant type of waste is waiting, caused by waiting for materials as needed, process queues due to the limited number of workers, and difficulty finding materials in an unorganized work area. The proposed improvements include improving communication with suppliers regarding material specifications, improving labor schedules and providing counseling and training on the application of the 5 S/R culture. With these proposed improvements, it is expected to increase the achievement of production targets in the Finishing department of PT XYZ.